THE PROBLEM OF STRENGTHENING SPHERICAL MENISCI - Смоляр, Анатолій; Мірошікіна, Ірина (SWorldJournal, 2022)
The problem of strengthening spherical menisci made of glass have been presented in the article. Spherical meniscuses are structural elements of various flying objects. Positive normal stresses in the near-surface layer are dangerous for meniscuses. The